Feather Christmas [videorecording (DVD)] - Matthews, Rebecca J.; Smith, Benny J.; Smith, Benny J.; O'Leary, Dan William; MacHell, Tom; Harris, Ocean M.; Duncan, Sarah Jane (Gravitas Ventures, 2024)
For single dad, Martin, Christmas is all about upholding regular family traditions. But when a pet chicken arrives at his home-run animal sanctuary, Martin's world is turned upside down, as new love blossoms and spreads its wings!